RELEVANT DEVELOPMENT DIRECTIONS OF FINANCIAL LAW AND FINANCIAL AND LEGAL PROFILE AT THE NORTH-CAUCASUS FEDERAL UNIVERSITY - D. A. Smirnov; L. Je. Botasheva (Гуманитарные и юридические исследования)
The article studies relevant development directions of inancial law and inancial and legal proile in the North-Caucasus Federal University. Practice of educational and scientiic activity of administrative and financial law department at the Institute of law, the North-Caucasus federal university, is given. The study of educational curricula and the competences formed with students is viewed as significant from the practical point. Subject matters and their modern educational methodological support are analyzed.